ANALISIS PENGARUH KESADARAN MEREK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KARTU PRABAYAR XL DI KALANGAN MAHASISWA (Studi pada Mahasiswa Universitas Diponegoro) - Anggana, Raihan Fakhrin; Idris, Idris (Diponegoro Journal of Management, 2017)
The problem that occurs is a decrease in the number of subscribers of the XL mobile telecommunication prepaid service. It is characterized by the number of subscribers of XL prepaid service are decrese from 60.172 to 42.100 in two years. And it also caracterized by the number of the other prepaid service providers are increased each year. This study is aimed to analyze the influence of brand awareness, price, and promotions to the customer buying decision in Diponegoro University Students. The population used in this study are all the students in Diponegoro University who has an experience with the XL prepaid service product with minimum six months use. The sampling technique used was purposive sampling. The samples that taken for this  study  is  125  respondents.  The  methods  of  data  collection  in  this  study  is  by  using questionnaires that the author gave directly to the respondents. Based on this research, brand awareness, price, and promotion has a positive influence to costumer buying decision for the XL prepaid telecommunication service in the students of Diponegoro University. The variable   that used in this research that has biggest influence to the XL postpaid product buying decision is promotion  and the  variable  that  has smallest  influence  to  the  XL postpaid product  is  brand awareness.